Schistosomiasis drug therapy and treatment considerations. - Shekhar, K.C. (1991)
Schistosomiasis, a grave and debilitating disease of socioeconomic importance, is increasing in incidence despite concerted efforts to control and contain the disease in all the endemic areas. While a multipronged method of control using health education, sanitation and snail control has been used, chemotherapy and chemoprophylaxis play the most important and crucial role in containing/preventing the transmission of the disease. Schistosomicides such as antimonials were introduced, as early as the 1990s as the drugs of choice and continued to be used until the early 1960s. The antimonials were administered intravenously, and produced severe side effects; the various variables that determined their effects at the site of action made their application difficult and adversely affected their use in large scale chemotherapy. The antimonials were then replaced by hycanthone and lucanthone which were administered intramuscularly. These drugs produced immediate side effects such as hepatotoxicity and gastrointestinal disturbances, and were consequently withdrawn. It was then decided that the alternative was to produce synthetic drugs that could be administered orally. Niridazole, oxamniquine, and metrifonate were introduced as schistosomicidal agents, with drugs like oltipraz and amoscanate still at clinical trial phase. Therapeutic doses of drugs like hycanthone, niridazole and amoscanate have been found to cause many major side effects. A significant advance in the control of schistosomiasis chemotherapy is the introduction of a relatively safe, effective, broad spectrum oral helminthic agent, praziquantel. Studies have also shown that oxamniquine is as effective as praziquantel in eliminating intestinal S. mansoni infection, and metrifonate is as effective as praziquantel in eliminating urinary S. haematobium and S. mansoni infections. Praziquantel has been found to be effective in treating S. haematobium infections compared with metrifonate and more effective in treating S. mansoni infection when compared with oxamniquine. Because the drug is effective even when treating advanced hepatosplenic schistosomiasis, with few side effects, praziquantel is currently the drug of choice for the treatment of any kind of schistosomiasis. The only limitation is the cost which restricts its use in many developing countries. While effective, safe drugs for mass chemotherapy are being developed, the problem of therapeutic failure and drug resistance is being reported from certain developing countries. Under these circumstances, alternative drugs must be resorted to. Mass treatment, a crucial goal in the eventual control of schistosomiasis, awaits a well-tolerated and nontoxic drug that will ultimately prove to be effective where cure is definite. Until such a time, while eradication of the disease is a near impossibility, reducing the intensity of infection can ultimately reduce morbidity and even mortality.(ABSTRACT TRUNCATED AT 400 WORDS)